Parameterized Animation Compression - Hakura, Ziyad S.; Lengyel, Jerome E.; Snyder, John (Proceedings of the Eurographics Workshop on Rendering Techniques, 2000)
We generalize image-based rendering by exploiting texture-mapping graphics hardware to decompress ray-traced “animations”. Rather than 1D time, our animations are parameterized by two or more arbitrary variables representing view/lighting changes and rigid object motions. To best match the graphics hardware rendering to the input ray-traced imagery, we describe a novel method to infer parameterized texture maps for each object by modeling the hardware as a linear system and then performing least-squares optimization. The parameterized textures are compressed as a multidimensional Laplacian pyramid on fixed size blocks of parameter space. This scheme captures the coherence in parameterized animations and, unlike previous work, decodes directly into texture maps that load into hardware with a few, simple image operations. We introduce adaptive dimension splitting in the Laplacian pyramid and separate diffuse and specular lighting layers to further improve compression. High-quality results are demonstrated at compression ratios up to 800:1 with interactive playback on current consumer graphics cards. https://youtu.be/a0F19zwkNL0 https://youtu.be/TGvayFUpmqI https://youtu.be/H3HDAaqsLHw https://youtu.be/GhYxA4dY-LU https://youtu.be/eT8lo3kskdQ https://youtu.be/d3UVsjeoT7I https://youtu.be/-VWCvoRpt2Q https://youtu.be/P4xCcbrg2aU https://youtu.be/yvjNF3_OSnE https://youtu.be/tA8DcpJmQgA https://youtu.be/3mYeCF4PhfU https://youtu.be/cIpWTi2MqcQ